Study on copper incorporated mesoporous silica SBA-15 for N2O catalytic decomposition - Mohd Haizal, Mohd Husin (2016)
Nitrous oxide (N20) is an environmental pollutant because it is a relatively strong greenhouse effect gas and contributes towards the destruction of ozone in the stratosphere. Direct decomposition of N20 by catalysts represents one of the potential solutions to minimize N20 emissions. This research, focuses on Cu incorporation into SBA-15 mesoporous silica by pH modification method using hexamethylenetetrarnine (HMTA) as an internal pH-modifier and its potential use as a catalyst for N20 decomposition. The effect of acidity on SBA-15 preparation through different initial HC1 concentration and the addition of HMTA as pH modifier were investigated. The SBA-15 formed well-ordered hexagonal mesoporous structure at high acidity (2.0 M) and poor ordered hexagonal pore structure at low acidity condition (0.005 M). It was found that under moderate acidic condition (0.1 M HC1) with addition of HMTA (HMTA:Si molar ratio 1:10), well-ordered hexagonal mesoporous SBA-15 could be produced. Meanwhile, copper was chosen for further studies on metal incorporation of SBA-15 (M/SBA-15) because Cu-containing SBA-15 has the highest catalytic activity for N20 decomposition compared to that of other first row transition metals impregnated on SBA-15. Copper incorporated mesoporous silica (Cu-SBA-15) has been successfully prepared by direct synthesis under medium acidic condition with addition of HMTA as a pH modifier. The Cu/SBA-15 produced were characterised using XRD, N2 adsorption-desorption, TEM, SEM, FT-IR, UV-vi, XPS and TPR. The results indicate that Cu was mainly incorporated into the framework of SBA- 15. The unit-cell, surface area, pore volume and wall thickness increased after the incorporation of the copper ions in SBA-15. HMTA plays a very important role to increase internal pH in order to introduce copper into the framework of SBA- 15 silica. Cu loading on Cu/SBA- 15 determined using AAS is almost the same to the initial Cu amount, when the pH value is above isoelectronic of silica (pH=2) due to addition of HMTA. Higher amount of HMTA, however, lead to the destruction of SBA-15 structure. Compared with Cu/SBA-15 impregnation method, Cu/SBA-15 prepared through pH modification method shows much higher activity for N20 catalytic decomposition due to 80% N20 conversion at 550 °C and reached 100% at 600 °C. The activation energy for the reaction catalysed by Cu/SBA-15 prepared through pH modification method is 91.9 -121.6 kJ/mol. This is much lower compared to that catalysed by CU/SBA-15 prepared though impregnation, that is in the range between 148.5 - 173.9 kJ/mol. Cu/SBA-15 incorporated sample also has higher activity due catalytic activity started at 300 °C and reaches more 80% conversion at 500 °C for catalytic reduction of N 20 by CH4.